Propargyl Amides as Irreversible Inhibitors of Cysteine Proteases—A Lesson on the Biological Reactivity of Alkynes1. Issue 32 (21st June 2013) - Arkona, Christoph; Rademann, Jörg
<x xml:space="preserve">Abstract</x> Are aliphatic alkynes truly bioorthogonal? In an attempt to prepare clickable ubiquitin derivatives bearing a C‐terminal propargyl amide, two groups have now independently discovered propargylamides to be irreversible inhibitors of cysteine proteases. The unexpected findings demonstrate the unexpected reactivity of alkynes in protein‐templated reactions and introduce a novel class of activity‐based protein probes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>